Direct oral anticoagulant– vs vitamin K antagonist–related nontraumatic intracerebral hemorrhage. (12th September 2017) - Tsivgoulis, Georgios; Lioutas, Vasileios-Arsenios; Varelas, Panayiotis; Katsanos, Aristeidis H.; Goyal, Nitin; Mikulik, Robert; Barlinn, Kristian; Krogias, Christos; Sharma, Vijay K.; Vadikolias, Konstantinos; Dardiotis, Efthymios; Karapanayiotides, Theodore; et al.
Abstract : Objective: To compare the neuroimaging profile and clinical outcomes among patients with intracerebral hemorrhage (ICH) related to use of vitamin K antagonists (VKAs) or direct oral anticoagulants (DOACs) for nonvalvular atrial fibrillation (NVAF). Methods: We evaluated consecutive patients with NVAF with nontraumatic, anticoagulant-related ICH admitted at 13 tertiary stroke care centers over a 12-month period. We also performed a systematic review and meta-analysis of eligible observational studies reporting baseline characteristics and outcomes among patients with VKA- or DOAC-related ICH. Results: We prospectively evaluated 161 patients with anticoagulation-related ICH (mean age 75.6 ± 9.8 years, 57.8% men, median admission NIH Stroke Scale [NIHSSadm ] score 13 points, interquartile range 6–21). DOAC-related (n = 47) and VKA-related (n = 114) ICH did not differ in demographics, vascular risk factors, HAS-BLED and CHA2 DS2 -VASc scores, and antiplatelet pretreatment except for a higher prevalence of chronic kidney disease in VKA-related ICH. Patients with DOAC-related ICH had lower median NIHSSadm scores (8 [3–14] vs 15 [7–25] points, p = 0.003), median baseline hematoma volume (12.8 [4–40] vs 24.3 [11–58.8] cm 3, p = 0.007), and median ICH score (1 [0–2] vs 2 [1–3] points, p = 0.049). Severe ICH (>2 points) was less prevalent in DOAC-related ICH (17.0% vs 36.8%, p = 0.013). In multivariable analyses, DOAC-related ICH was independently associated with lower baseline hematoma volume ( p = 0.006), lower NIHSSadm scores ( p = 0.022), and lower likelihood of severe ICH (odds ratio [OR] 0.34, 95% confidence interval [CI] 0.13–0.87, p = 0.025). In meta-analysis of eligible studies, DOAC-related ICH was associated with lower baseline hematoma volumes on admission CT (standardized mean difference = −0.57, 95% CI −1.02 to −0.12, p = 0.010) and lower in-hospital mortality rates (OR = 0.44, 95% CI 0.21–0.91, p = 0.030). Conclusions: DOAC-related ICH is associated with smaller baseline hematoma volume and lesser neurologic deficit at hospital admission compared to VKA-related ICH.